METHODOLOGICAL FOUNDATIONS OF PLANNING AND EVALUATING FIELD TRAINING - Odiljon Tobirov,; Xidoyatkhon Abdinazarova,; Azamjon Jobborov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the methodological foundations of planning and evaluating field training, emphasizing the role of structured frameworks in enhancing training effectiveness and accountability. Drawing on established evaluation models and contemporary methodological approaches, the study examines key stages of field training design, including objective setting, data collection, monitoring, and outcome assessment. Special attention is given to the integration of qualitative and quantitative evaluation  tools,  such  as  pre-  and  post-training  assessments,  performance-based metrics,  and  feedback  mechanisms,  which  together  provide  a  comprehensive understanding of training impacts. The analysis highlights the importance of iterative evaluation  and  evidence-based  decision-making  in  improving  professional competencies and practical readiness. The findings suggest that adopting systematic, adaptable,  and  data-driven  methodologies  significantly  strengthens  the  quality  and sustainability  of  field  training  programs,  supporting  continuous  improvement  and informed management practices.